Improving Students’ Writing Ability by Application of Semantic Mapping Strategy at SMA Muhammadiah - Hetty Zaharani (Universitas Potensi Utama, 2022)
Writing skill is one of the most important skills in English to communicate information or something through media like paper, email, book, etc. Excellent writing skill allows the students to express their opinions, thoughts, and imagination. The result is to make the readers understand and attract to their writing. Writing activities make every writer think, learn and communicate in the media. Unfortunately, most of the students face difficulty and stagnant in writing. They need some strategies to help them in improving their writing skill. Semantic mapping is one of the effective ways for improving writing ability. It helps students to get an idea and improve it into sentences and paragraphs. This study described the use of semantic mapping in teaching writing skills. This study is aimed to improve student's language skills, especially writing based on their literacy level. It also applied semantic mapping in the joint construction of the text. Students were asked to write the report after they created a semantic mapping of their idea and group. The method of this study was action research which had four steps. The steps were planning, acting, observing, and reflecting. The data was collected from the cognitive test, observation checklist, questionnaire, and interview. The purpose of the research is to know whether using a semantic mapping strategy can improve the students’ writing skills. This study is a classroom action research and It focuses on how students respond to semantic mapping strategy in English writing skills. The instrument of this study is using a questionnaire which is distributed to the students of the academic year 2021/2022 that consisted of 30 students in XII grade, 17 females and 13 males. The result of this study was 90,33 % of students got easier in learning writing tasks and 26,33% had great enthusiasm to master writing skills by using semantic mapping strategy.